Tinjauan Literatur: Intervensi Suplemen Makanan untuk Meningkatkan Z-Skor PB/U pada Balita Stunting: Literature Review: Food Supplement Intervention to Increase Z-Score Height for Age in Stunting Children - Maya Fernandya Siahaan; Auni Rahmatika; Siti Rahayu Nadhiroh (Amerta Nutrition, 2023)
Background: Stunting is a chronic growth disorder that occurs during growth and early development in life. Interventions to prevent malnutrition should be implemented within 1000 days of life. Between 6 and 24 months is essential as children transition from exclusive breastfeeding to complementary feeding.  Objectives: To provide scientifically justifiable information on dietary preventions to prevent stunting. Discussions: The data were obtained from a study of various literature sources by searching through search engines: Google Scholar, BMC, Pubmed, and ScienceDirect, in the form of research results of reputable and national journals. The articles obtained related to this study were seven articles related to dietary supplement interventions to increase the z-score of Length/height-for-Age in stunted children aged 6-24 months. Conclusions: There were two types of interventions carried out to increase the HAZ in stunting toddlers by providing a single nutrient (mineral zinc) and a combination of 2-3 types of nutrients (Zinc, Iron, Vitamin B12, Vitamin A, Fat). In contrast, the intervention of the combination of zinc mineral nutrients, prebiotics, and food supplements in the form of micronutrient powder sachets did not show a significant difference in the length gain of toddlers.